Kaskade predpisovanja zdravil - Ravbar, Nina (Farmacevtski vestnik, 2023)
A prescribing cascade begins when a drug is prescribed, an adverse drug reaction occurs that is misinterpreted as a new medical condition, and a subsequent drug is prescribed to treat this druginduced adverse reaction. while some prescribing cascades can be intentional, unintentional prescribing cascades are problematic as they can result in prescribing unnecessary additional drugs. This increases the risk of adverse drug reactions and potential drug interactions, which can impact the patient’s quality of life. Additionally, unnecessarily prescribed drugs also represent additional costs that burden the healthcare system. while various examples of prescribing cascades have been published, their clinical importance is often not evaluated. Increasing efforts are aimed at creating lists of clinically significant prescribing cascades, with the help of different experts and consensus-building methods. In addition to known prescribing cascades, it is also important to identify new ones, which can be done by using the prescription sequence symmetry analysis, enabling the detection of potential prescribing cascades using databases.
Keywords: Ambulantno predpisovanje; analiza simetričnosti sekvenc predpisovanja; klinično pomembne kaskade predpisovanja; neprimerno predpisovanje; neželeni učinek; Neželeni učinki; Starejši ljudje; starejši odrasli